DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF LAMIVUDINE AND ZIDOVUDINE IN BULK - Kamala, Govindarao; Vadrevu, Sowjanya; Valli, K. Naga (International Journal of Current Pharmaceutical Research, 2016)
Objective: The scope of the present work is to expand and optimization of the chromatographic conditions and to develop RP-HPLC method. Methods: The method was performed with various columns like C18 column, kromasil column, Hypersil BDS column. Among them, Symmetry C18 (250x4.6 mm, 5um) was found to be ideal as it gave good peak shape at 0.8 ml/min flow and validated for various parameters such as linearity, precision, accuracy, System suitability, Specificity, % Assay, Robustness, etc. Results: The system suitability parameters were evaluated from standard chromatograms by calculating the % RSD from five replicate injections for Lamivudine and Zidovudine retention times and peak areas. The % RSD for the retention times of principal peak from 5 replicate injections of each standard solution were less than 2.0 %. The Linearity and correlation coefficient of Lamivudine and zidovudine was found to be 0.999. Precision was performed and % RSD for Lamivudine and Zidovudine were found to be less than 2.0. The % Recovery for each level was found to be the range of 98.0 to 102%. In Robustness, the % RSD of the peak area of all peaks for five replicate injections should be not more than 2.0. Conclusion: Hence, the chromatographic method developed for Lamivudine and Zidovudine is said to be rapid, simple, specific, sensitive, precise, accurate and reliable that can be effectively applied for routine analysis in research institutions, quality control department in industries, approved testing laboratories, bio-pharmaceutics and bio-equivalence studies and in clinical pharmacokinetic studies.